An Evolutionary View of Trypanosoma Cruzi Telomeres - Ramirez, Jose Luis (Frontiers in Cellular and Infection Microbiology, 2020)
Like most eukaryotes the linear chromosomes of the parasite Trypanosoma cruzi end in a nucleoprotein structure called the telomere, which in turn is preceded by regions of variable length called subtelomeres. Together telomeres and subtelomeres are dynamic sites where DNA sequence rearrangements can occur without compromising essential interstitial genes or chromosomal synteny. Good examples of subtelomeres involvement is the expansion of human olfactory receptors genes, variant surface antigens in Trypanosoma brucei, and Saccharomyces cerevisiae mating types. T. cruzi telomeres are made of long stretches of the hexameric repeat 5'-TTAGGG-OH-3', and its subtelomeres are enriched in genes and pseudogenes from the large gene families RHS, TS and DGF1, DEAD/H-RNA helicase and N-acetyltransferase, intermingled with sequences of retrotransposons elements. In particular, members of the Trans-sialidase type II family appear to have played a role in shaping the current T. cruzi telomere structure. Although the structure and function of T.cruzi telomeric and subtelomeric regions have been documented, recent experiments are providing new insights into T. cruzi's telomere-subtelomere dynamics. In this review, I discuss the co-evolution of telomere, subtelomeres and the TS gene family, and the role that these regions may have played in shaping T. cruzi's genome.